Consequences of Bullying in the Formation of Students According to Latin American Studies Between 2010-2021 - Caicedo Bohórquez, Leidy Xiomara (2022)
This paper shares a state of knowledge about the consequences generated by bullying in the formation of school-age students according to studies in Latin America between 2010-2021. The method consisted of a documentary review of 34 files which comprise undergraduate, master's, and doctorate theses, and published scientific articles. The analysis of the information was carried out under a documentary matrix that contrasted the data in relation with two study categories: 1) Bullying as a scientific interest and 2) Consequences generated by bullying in school age. The main result shows that bullying causes low self-esteem, depression, anxiety, poor school performance and somatic symptoms in the victims, which, if not treated in a timely manner at school and with the family, may result in the removal of the student from the institution denying them the right to education, or they could cause a most serious problem, suicide. As a conclusion, it is highlighted that bullying is triggered in a slow and tortuous process, which becomes more acute over time; it is the reason why care routes are necessary to tackle the problem from its first manifestations.